2005
DOI: 10.1158/0008-5472.can-04-3272
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Conditional Knockout of the Type II TGF-β Receptor Gene in Mammary Epithelia on Mammary Gland Development and Polyomavirus Middle T Antigen Induced Tumor Formation and Metastasis

Abstract: Transforming growth factor-B (TGF-B) isoforms are growth factors that function physiologically to regulate development, cellular proliferation, and immune responses. The role of TGF-B signaling in mammary tumorigenesis is complex, as TGF-B has been reported to function as both a tumor suppressor and tumor promoter. To elucidate the role of TGF-B signaling in mammary gland development, tumorigenesis, and metastasis, the gene encoding type II TGF-B receptor, Tgfbr2, was conditionally deleted in the mammary epith… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
209
3

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 229 publications
(236 citation statements)
references
References 30 publications
(27 reference statements)
19
209
3
Order By: Relevance
“…Recently, convincing evidence of interactions between individual genes or categories of genes (e.g., enzymes) in neoplastic and nonneoplastic cells within tumors has appeared in some reports. 16,[36][37][38][39][40] Moreover, Creighton et al 41 conducted global gene expression analysis and showed a network of tumor-stromal molecular interactions in a primary tumor xenograft model of lung cancer. Our current report now provides specific evidence that, during metastasis, labeled cancer cells and neighboring host cell lineages of 3 different organs (breast, lung and lymph node), reproducibly and reciprocally alter the expression of multiple groups of genes coordinately, upon encountering each other and/or the intercellular materials that they produce.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, convincing evidence of interactions between individual genes or categories of genes (e.g., enzymes) in neoplastic and nonneoplastic cells within tumors has appeared in some reports. 16,[36][37][38][39][40] Moreover, Creighton et al 41 conducted global gene expression analysis and showed a network of tumor-stromal molecular interactions in a primary tumor xenograft model of lung cancer. Our current report now provides specific evidence that, during metastasis, labeled cancer cells and neighboring host cell lineages of 3 different organs (breast, lung and lymph node), reproducibly and reciprocally alter the expression of multiple groups of genes coordinately, upon encountering each other and/or the intercellular materials that they produce.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, knockout of TGFBR2 in the fibroblasts of the tumor microenvironment resulted in upregulation of HGF, MSP, TGF-a, and other secreted factors that significantly en-98 npg hanced the adjacent epithelial cells to proliferate [5,96]. Surprisingly, these studies show that TGFBR2 knockout animals developed significantly more pulmonary metastases compared with control mice [35,[97][98][99]. In a recent report, researchers have shown that targeted deletion of TGFBR2 in mouse mammary epithelium initiates the recruitment of myeloid immune suppressor cells through the CXCL5 axis.…”
Section: Mouse Models Of Tgfβ and Metastasismentioning
confidence: 96%
“…However, experiments in mice reveal that TGFb is not a universal proliferation regulator; rather TGFb elicits its antiproliferative effects in specific contexts. For example, tissue-specific inactivation of TGFBR2 in mouse models rarely leads to spontaneous tumor formation with little to no pathology in mouse mammary epithelium, oral cavity esophagus, forestomach, pancreas, intestine, and skin [35][36][37][38][39]. Instead, TGFb's potent anti-proliferative effects only become apparent under conditions of tissue injury or oncogenic stress.…”
Section: Tgfβ Tumor-suppressive Functionsmentioning
confidence: 99%
See 1 more Smart Citation
“…During pregnancy, there is a three-fold increase in apoptosis in ductal and alveolar cells from Tgfb1 heterozygote compared to wild-type (WT) mouse mammary glands (Ewan et al, 2002). Postpubertal mice in which Tgfbr2 was conditionally deleted in the mammary gland also exhibit a much higher rate of apoptosis compared to controls (Forrester et al, 2005). Reports using cancer cells and/or transgenic mammary tumors further support a role for TGFb in the suppression of apoptosis (Huang et al, 2000;Muraoka et al, 2003).…”
Section: Introductionmentioning
confidence: 97%